Contribution of Flora Biodiversity to Reducing Air Pollution Levels in Jambangan Village, Surabaya: Kontribusi Keanekaragaman Hayati Flora terhadap Penurunan Tingkat Pencemaran Udara di Kelurahan Jambangan, Surabaya - Putra Ardiansyah; Achmadi Susilo; Indarwati (Journal of Applied Plant Technology, 2026)
Air pollution is a major environmental problem in urban areas that affects human health and the environment. One natural way to reduce air pollution is through the use of floral biodiversity. This study aims to identify the level of plant diversity, the ecological role of flora in reducing air pollution, and the supporting and limiting factors in Jambangan Sub-district. The research was conducted in RW 02 and RW 03 using a qualitative descriptive method through observation, interviews, and documentation. Data were analyzed using the Shannon–Wiener diversity index, evenness index, and dominance index. The results show that plant diversity in the study area is high, with index values of 2.95 in RW 02 and 2.93 in RW 03. Flora plays an important role in absorbing carbon dioxide, producing oxygen, trapping dust particles, and improving the microclimate. Supporting factors include community participation and the availability of green open spaces, while limiting factors include limited land, high building density, and lack of plant maintenance. Improvement efforts can be made through greening programs, environmental education, proper plant selection, and support from local government policies.